Kepailitan sebagai Konsekuensi Pelanggaran Itikad Baik dalam PKPU: Kajian Yuridis terhadap Putusan Pengadilan Niaga dan Mahkamah Agung - Kuwayyis Wijaya, Laela; Nadhira Rahma, Nasya; Ruben Pendang, Serlita; Ghifari, Amaranila (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Suspension of Debt Payment Obligations (PKPU) is a legal mechanism aimed at providing debtors the opportunity to restructure their financial obligations through a settlement agreement with creditors. In practice, however, PKPU is often misused by parties acting in bad faith either debtors seeking to delay payments or creditors aiming to pressure debtors. Violation of the principle of good faith in PKPU may lead to legal consequences in the form of bankruptcy, as stipulated in Law Number 37 of 2004 concerning Bankruptcy and PKPU. This study aims to analyze the application of the principle of good faith in PKPU proceedings and to examine the legal considerations of the Commercial Court and the Supreme Court in declaring bankruptcy as a result of such violations. The research employs a normative juridical method with statutory and case approaches, focusing particularly on Supreme Court Decision Number 704 K/Pdt.Sus-Pailit/2017. The findings indicate that violations of the good faith principle serve as a valid ground for the court to declare a debtor bankrupt due to abuse of PKPU proceedings. Therefore, the principle of good faith plays a crucial role in maintaining integrity, fairness, and balance between debtors and creditors in Indonesia’s debt settlement process.